A review of KLF4 and inflammatory disease: Current status and future perspective - Yidan Liang; Jiamin Zhao; Tengkun Dai; Xin Li; Longqin Chen; Zhixu He; Mengmeng Guo; Juanjuan Zhao; Lin Xu (Elsevier, 2024)
Inflammation is the response of the human body to injury, infection, or other abnormal states, which is involved in the development of many diseases. As a member of the Krüppel-like transcription factors (KLFs) family, KLF4 plays a crucial regulatory role in physiological and pathological processes due to its unique dual domain of transcriptional activation and inhibition. A growing body of evidence has demonstrated that KLF4 plays a pivotal role in the pathogenesis of various inflammatory disorders, including inflammatory bowel disease, osteoarthritis, renal inflammation, pneumonia, neuroinflammation, and so on. Consequently, KLF4 has emerged as a promising new therapeutic target for inflammatory diseases. This review systematically generalizes the molecular regulatory network, specific functions, and mechanisms of KLF4 to elucidate its complex roles in inflammatory diseases. An in-depth study on the biological function of KLF4 is anticipated to offer a novel research perspective and potential intervention strategies for inflammatory diseases.